Reinventing Romanitas: Exchanges of Classical Antiquities as Symbolic Gifts between Italy and Spain (1933-1943) - Plantzos, Dimitris; Balaskas, Vasileios (Amsterdam University Press, 2023)
Based on fresh archival research this article examines the exchange of Romanizing statuary between Italy and Spain during the ventennio fascista. Between 1933 and 1943, Italy and Spain exchanged copies of Roman statues as symbolic gestures, to substantiate their claims to a shared classical heritage of ‘imperial greatness’. Using press reports and documentary film excerpts the article reconstructs public events that took place in Merida, Tarragona, Palma, and Zaragoza and assesses their impact. Behind these exchanges, and public ceremonies staged on their occasion, lay the Fascist concept of romanità: an archaeologically and aesthetically charged discourse placing Late-Republican and Early-Imperial Roman heritage in the epicentre of Fascist identity politics. Through improvised public performances of romanità, classical materialities, monumental as well as spatial, were imbued with Fascist dynamics, as the past turned into the present and projected into the future. Through individual and collective performance these ceremonies embodied a primeval Fascist ideal that appeared at once spectacular and modern.
Keywords: Arqueología romana; Fascismo; Propaganda política; Fascism; Classical antiquity; Roman heritage; Romanità